ANALYSIS ON THE PROVISION OF LEGAL REQUIREMENT FOR THE ESTABLISHMENT OF THE SHARĪᶜAH COMMITTEE OF ISLAMIC BANKS IN MALAYSIA - Hussain, Mohammad Azam; Hassan, Rusni (CENTRAL ASIA AND THE CAUCASUS, 2021)
The formation of the Sharῑᶜah committee in the Islamic banks is crucial in ensuring the Islamic banking business carried out by the Islamic banks comply with Sharῑᶜah principles. In Malaysia, the setting up of this committee is a statutory requirement to be observed by Islamic banks. By using legal research methodology, this study seeks to analyse the provision of legal requirement for the establishment of Sharīᶜah committee of Islamic banks in Malaysia. By employing analytical and critical analysis on the relevant legal provision, this study found that, the provision of law is significant which requires the Islamic banking institutions and participating banking institutions offering Islamic banking schemes to establish Sharīᶜah committee in order to ensure the Sharīᶜah compliance in relation to Islamic banking business. However, several legal issues pursuant to the general nature of the respective legal provision need to be attended by the relevant authority. These include the definition, the terminology used and the composition of the Sharῑᶜah committee as well as its position in the Islamic banks’ organisation structure.